Non-selective regulation of peroxide and superoxide resistance genes by PerR in Campylobacter jejuni - Kim, Jong-Chul; Oh, Euna; Hwang, Sunyoung; Ryu, Sangryeol; Jeon, Byeonghwa (Frontiers in Microbiology, 2015)
Campylobacter jejuni is an important foodborne pathogen. The molecular mechanisms for the regulation of oxidative stress resistance have not yet been understood fully in this bacterium. In this study, we investigated how PerR (peroxide stress regulator) modulates the transcriptional regulation of both peroxide and superoxide resistance genes in C. jejuni, particularly under oxidative stress conditions. The transcriptional levels of ahpC, katA, and sodB were substantially increased by aeration and oxidant exposure. Interestingly, a perR mutation completely abrogated the transcriptional response of ahpC, katA and sodB to oxidants. Furthermore, we demonstrated that perR transcription was reduced by aeration and oxidant exposure. In contrast to the unique role of PerR homologs in peroxide stress regulation in other bacteria, interestingly, C. jejuni PerR directly regulates the transcription of sodB, the most important gene in superoxide defense, as evidenced by the alteration of sodB transcription by the perR mutation and direct binding of rPerR to the sodB promoter. In addition, we also observed notable morphological changes in C. jejuni from spiral rods to coccoid morphology under aerobic conditions. Based on the intracellular ATP levels, C. jejuni entered a viable-but-non-culturable state under aerobic conditions. These findings clearly demonstrate that C. jejuni possesses a unique regulatory mechanism of oxidative stress defense that does not specifically distinguish between peroxide and superoxide defense, and PerR plays a pivotal role in this non-selective regulation of oxidative stress resistance in C. jejuni.